First detection and molecular characterization of Chaphamaparvovirus galliform in broiler and turkey flocks in Türkiye - Aslan, Ahsen Nisa; Abayli, Hasan; Tonbak, Sukru; Ongor, Hasan; Unal, Akin; Akan, Mehmet; Yalcinkaya, Ertug (Bmc, 2025)
BackgroundA newly uncovered parvovirus, Chaphamaparvovirus, continues to be reported across various species. This study investigated the detection and genetic characterization of Chaphamaparvovirus galliform (GaChpV) in poultry, specifically broilers and turkeys, from various regions in T & uuml;rkiye. To address this, comprehensive sampling and analysis were conducted to better understand the virus's distribution and impact in these avian populations.ResultsIn 2023, a total of 1060 fecal samples were collected from 76 broiler flocks (10 healthy and 66 with enteritis) and 30 turkey flocks (10 healthy and 20 with enteritis). Using nested PCR with specific primer sets, the study detected GaChpV in 36 out of 76 broiler flocks (47.3%) and 2 out of 30 turkey flocks (6,6%). Although GaChpV was detected at notable frequencies, the analysis revealed no statistically significant association between GaChpV and enteritis cases (p = 0.617). In this study, the nucleotide sequences (nt) of the capsid genes from GaChpV strains isolated from broilers and turkeys were 99 to 100% identical. Furthermore, these strains exhibited a high degree of genetic similarity ranging from 73 to 98% to Chaphamaparvovirus galliform 2 (GaChpV-2) strains from Europe, China, and Brazil. Complete genome sequencing of a broiler strain (CkChPV/2023/UN-2-TR) yielded a genome of 4,229 nucleotides, with sequence identity ranging from 78.93 to 98.82% compared to other GaChpV strains. Phylogenetic analysis further revealed that the CkChPV/2023/UN-2-TR strain clustered with GaChpV-2 strains, highlighting its genetic relatedness and diversity within the GaChpV family. The study also investigated genetic recombination signals and identified potential B-cell linear epitopes, contributing to a better understanding of the virus's genetic diversity and antigenic characteristics.ConclusionsThis report represents the first detection of GaChpV in turkey and broiler flocks in T & uuml;rkiye. Notably, research on this topic in turkeys is quite limited. The data derived from this study will contribute to elucidating the molecular epidemiology and evolutionary dynamics of GaChpV.
Keywords: Chaphamaparvovirus; Broiler; PCR; Turkey; T & uuml;rkiye